Bioactive Sutures: A Review of Advances in Surgical Suture Functionalisation - Alshomer, Feras; Madhavan, Arul; Pathan, Omar; Song, Wenhui (Current Medicinal Chemistry, 2017)
Sutures have been at the forefront of surgical medicine throughout time. With recent advances in suture technology, it is possible to incorporate biologically active substances to enhance suture function and capability. Bioactive sutures represent a modality interest in controlled drug and cell delivery to traumatic sites. In this article, a comprehensive literature search of key bibliographic databases focusing on suture material fabrication and advanced modification was performed. The history, manufacturing process and cost-effectiveness of bioactive sutures are presented. Several novel modifications to enhance function in drug and growth factor delivery and cell therapy are also reviewed. Different antimicrobial drugs and anaesthetics have been shown to be effective in reducing inflammation and bacterial infection. Cellular therapy represents a unique modality augmenting the surgical repair of various soft tissue injuries. We propose a definition of bio-active sutures as biomaterials that are engineered to have controlled tissue interaction to optimise wound/defect healing, in addition to their essential function in tissue approximation.
Keywords: wounds